EXPLORING THE IMPACT OF LEADERSHIP STRATEGIES ON CORPORATE SUSTAINABILITY: INSIGHTS FROM PROFITABILITY, ETHICAL GOVERNANCE, AND LONG-TERM VALUE CREATION - Ruslaini, Ruslaini; Benardi, Benardi; Agustinus, Rendy (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
This study aims to explores the impact of leadership strategies on corporate sustainability, focusing on profitability, ethical governcance, and long-term value creation. The study population consists of individuals occupying leadership positions in various corporation. The purposive sampling technique is used to select participants with extensive and insights into the interaction between leadership strategies and corporate sustainability. Data analysis involves thematic analysis to identify patterns, themes, and meaning within textual data. Through in-dept interviews, several key themes emerged, elucidating how leadership strategies influence corporate sustainability dimensions. Ethical leadership, strategic alignment of financial and sustainability goals, effective corporate governance, and transparent communication were identified as key drivers of sustainable business practices. Findings underscore the imperative for organizational to adopt a holistic apporoach to business, integrating sustainability principles into their core values and strategic decision-making process. By embracing these principles, organizations can enhance their long-term resilience, competitiveness, and contribution to society and the environment.